Dampak positif kurikulum merdeka terhadap mata pelajaran bahasa Indonesia - Nurhuda, Pradicta (Fakultas Sastra, 2023)
Abstrak: Indonesian is a subject that must be studied at every level of education so that with the enactment of the current Merdeka Curriculum it will not change or eliminate Indonesian as a compulsory subject. The Merdeka Curriculum certainly has positive and negative impacts on all subjects when viewed from a certain point of view. This study aims to determine the positive impact of the Merdeka Curriculum on Indonesian subjects. This study uses a qualitative research method with a literature study approach. The results of the study show that the positive impact of the Merdeka Curriculum on Indonesian subjects is (1) internalizing the profile of Pancasila students; (2) the students' language skills are increased; and (3) the learning flow is more flexible and not rigid. Keywords: Impact, Positive, Merdeka Curriculum, Indonesia Language